Electoral manipulations and fraud political contestation: The case of regional head election - Habibi, Muhammad; Nurmandi, Achmad (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Political contestation in the context of the General Election is related to the importance of the role of constituents as the owner of sovereignty, especially to guarantee the quality of an election. However, in practice, the critical role of the constituents seems to be an irony when elites who fight as actors are trapped in a latent condition. That shows there is a misconception in interpreting the nature of power and how to get it. For the actors, the post-conflict local election is only a means to gain political power superficially and ignore other things. Therefore, cheating in political contestation also seems to be necessary for those who think it is rational.